0046 Circadian misalignment is associated with Covid-19 infection. (25th May 2022) - Coelho, Julien; Micoulaud-Franchi, Jean-Arthur; Nguyen, Duc; Wiet, Anne-Sophie; Taillard, Jacques; Philip, Pierre
Abstract: Introduction: Sleep disturbances are frequently reported in patients infected by Covid-19, but the role of sleep-wake behaviors as a risk factor to contract Covid-19 has up to now poorly been studied. The aim of this study was to explore the relationship between usual sleep-wake behaviors and the risk of Covid-19 infection in a population of subjects suspect of contact or infection with SARS-CoV-2. Methods: Cross-sectionnal monocentric study set during a non-confined period in winter 2021. Recruitment took place in a Covid-19 ambulatory screening platform. Subjects between 18 and 45 years old were included whether they were symptomatic or not, healthcare workers or not, in contact with a Covid-19 case or not. They were asked about their usual sleep-wake behaviors. Usual sleep duration and sleep timing were explored during workdays and free days. Circadian misalignment was defined as at least 2 hours shift of circadian alignment (defined as the difference between mid‐sleep during workdays and mid‐sleep during free days, mid sleep as the middle between bedtime and getting up time). Results: One thousand eighteen subjects were included in our study (acceptance rate: 10.8%, 39% of men, mean age of 28±8). Habitual mean sleep duration was equivalent in both groups (7h47 vs 7h49, p=0.733). Circadian misalignment greater than 2 hours concerned 33% of subjects in the Covid-19 group versus 20% of the control group (p=0.026). After adjustment on age, gender, BMI and work schedules, subjects presenting a circadian misalignment superior to 2 hours had 2.07 more chances to be tested positive than subjects which respected on identical sleep-wake timing between workdays and free days (OR=2.07, 95%CI= [1.12-3.80], p=0.024). Conclusion: Altered sleep not only is present in subjects infected by Covid-19 but could be responsible of a higher change to be infected. Chronobiological impact on immune system and higher chances to be exposed to social contacts could explain our findings which deserve to be confirmed through a future large cohort study. Ultimately regular sleep-wake pattern could constitute a privileged prevention target to fight Covid-19 infection. Support (If Any):